Sentinel lymph nodes in endometrial cancer update 2018 - Ibrahim A Abdelazim; Mohannad Abu-Faza; Gulmira Zhurabekova; Svetlana Shikanova; Bakyt Karimova; Mukhit Sarsembayev; Tatyana Starchenko; Gulmira Mukhambetalyeva (Wolters Kluwer Medknow Publications, 2019)
There are no established data about lymphadenectomy during treatment of endometrial cancers (ECs) and to what extent lymphadenectomy should be performed. In addition, retroperitoneal lymphadenectomy increases the intraoperative and postoperative complications. Sentinel lymph node (SLN) mapping has the lowest costs and highest quality-adjusted survival. SLN is the most cost-effective strategy in the management of low-risk ECs. Women staged with SLN mapping were more likely to receive adjuvant treatment compared with women staged with systemic lymphadenectomy. This review article designed to evaluate the diagnostic accuracy and the methods of SLN detection in ECs.